INHIBITIVE BEHAVIOUR OF GREEN INHIBITOR IN POTABLE WATER DISTRIBUTION SYSTEM (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
The inhibition effect of amino trimethylene phosphonic acid (ATMP) and zinc ions on the corrosion of carbon steel in potable water distribution system was investigated. The corrosion inhibiting action was studied through weight loss, potentiodynamic polarization and AC impedance spectroscopy techniques. The possibilities of formation of protective complex was examined using UV – visible spectroscopy. The investigations revealed that zinc acts as an excellent synergist in corrosion inhibition. UV – visible spectral study indicates that there will be a possibility of formation of complexes of ATMP and Zn2+ with carbon steel iron. Polarization studies indicate that the new binary system is a mixed inhibitor. Result of the impedance studies shows that a protective film is formed on the metal surface in presence of the inhibitor formulation.